Auditing referrals in an acute hospital to determine ward capability in common symptom management. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Harris, Andrea; Wheelhouse, Alison; Hunter, Noeleen; Walker, Jane; Nicholson, Alexander
Abstract : Background: General Palliative Care should be provided by the usual professional carers of the patient and family irrespective of specific roles. Where more complex needs are identified, the Specialist Palliative Care Team (SPCT) is available to offer support and advice. Palliative Care Guidelines have been published to support symptom management throughout the hospital trust and awareness of these is raised during doctor induction and education sessions. A perception by the SPCT was that referred patients often have had neither a basic assessment of symptoms nor a trial of first line symptom management. Seeking evidence to support or refute this perception and to determine more accurately where teaching priorities lie, an audit of referrals and referred patients' prior management was undertaken. Methods: 50 consecutive referrals and notes were audited against agreed criteria to determine what measures had already been implemented in four areas of physical symptom management (pain, nausea & vomiting, constipation and end of life symptom management) prior to the host team involving the SPCT. The measures expected to have been implemented by the generalist team were drawn directly from symptom control guidelines. Problems identified by SPCT were also compared with reason for referral. Results: In each of the four domains there was poor correlation between reason(s) for referral and problems identified on assessment. For example nausea and vomiting was a problem in 34% of cases but constituted only 4% of referrals. Likewise initial basic symptom management expectations were not fulfilled in any domain. Conclusion: SPCT perceptions were confirmed. Acute hospital generalist staff are not equipped with the core knowledge to initiate symptom assessment and introduce basic palliative care symptom measures. The SPCT will develop and deliver targeted 'micro-teaching' sessions on the four areas of expectation to bring all wards to a basic level of competency. Re-audit will follow.